Appropriate technology intervention for business development of Slondok Aredo in Magelang City - Prabowo, Nugroho Agung; Rusdjijati, Retno; Purnomo, Tuessi Ari (Community Empowerment, 2025)
Slondok is a popular snack from Magelang, made from cassava and characterized by its crispy, salty, sweet, and spicy flavors. Despite its popularity, there are a limited number of slondok-producing micro and small enterprises (MSEs) in Magelang. One such enterprise, Slondok Aredo, located in Tidar Sawe, still operates with traditional methods in its production process, marketing, and business management. This traditional approach has limited the enterprise's ability to achieve optimal business growth and improve the welfare of its owners. To address these challenges, this community empowerment initiative provides assistance to the MSE through an appropriate technology intervention. Through a combination of socialization, training, hands-on practice, and continuous mentoring, the MSE has implemented several changes that have significantly impacted its business development. These improvements include the adoption of an automatic mixer for the marination process, the use of a sealing machine for product packaging, the creation of a more ergonomic frying furnace, the implementation of a bookkeeping application, and the expansion of marketing efforts through social media. Additionally, the payment system was modernized with the introduction of QRIS for consumer transactions.